The effectiveness of the implementation of the Cape Triage Score at the emergency department of the National District Hospital, Bloemfontein - S.A.N. Gordon; H. Brits; J.E. Raubenheimer (South African Family Practice)
Background: The need for an appropriate South African triage system led to the development of the Cape Triage Score (CTS), a system to prioritise emergency departments’ workloads. This study evaluated the effectiveness of the CTS at the National District Hospital emergency department, Bloemfontein.